2014
DOI: 10.1080/09064710.2014.911953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic, low input, conventional management practices on soil nematode community under greenhouse conditions

Abstract: A comparative study of organic, low input, conventional vegetable greenhouse systems was conducted to assess the effect of management practices on the soil nematode community. Bacterivores were the most dominant trophic group in all three systems with a mean proportion of over 80%, followed by omnivore-carnivores. In general, organic management practices increased the abundance of total nematodes, bacterivores, fungivores, and omnivore-carnivores in comparison with low input and conventional management practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…A long-term experiment for vegetable growth was conducted beginning in March 2002 at Quzhou Experimental Station of China Agricultural University [7]. The experiment site was located in the north of Quzhou County (36 • 52 N, 115 • 01 E) in Handan City, Hebei Province, North China Plain.…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A long-term experiment for vegetable growth was conducted beginning in March 2002 at Quzhou Experimental Station of China Agricultural University [7]. The experiment site was located in the north of Quzhou County (36 • 52 N, 115 • 01 E) in Handan City, Hebei Province, North China Plain.…”
Section: Study Area and Experimental Designmentioning
confidence: 99%
“…At present, there are many studies on greenhouse vegetable production systems, mainly focusing on the agronomy and economic benefits of the cultivation modes [6] and microbial diversity [7]. Some researchers have also studied the environmental impact of greenhouse vegetable production, but have mainly focused on a certain aspect, such as greenhouse gas emissions [8] or pollution of reactive nitrogen [9].…”
Section: Introductionmentioning
confidence: 99%
“…These traditional vegetable production systems exhibit substantial water and fertilizer usage, accompanied by low efficiencies in water and nitrogen utilization (WUE and NUE) and large amounts of nitrate leaching [10,11]. Numerous studies have shown that optimizing N rates and adjusting water irrigation strategies can effectively reduce nitrate leaching in greenhouse vegetable fields [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed a negative effect of tillage on food web complexity (Ugarte et al, 2013), an increase in overall abundance of nematodes in response to organic matter inputs (Li et al, 2014), and strong correlations between soil nutrient status and the number of bacterivores Pan et al, 2010). Crop type was shown to affect composition of nematode assemblages to a larger extent than farming system Neher, 1999).…”
Section: Introductionmentioning
confidence: 99%